2017
DOI: 10.3389/fmicb.2017.01817
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Gene Turnover as a Significant Source of Genetic Variation in a Recently Seeded Population of a Healthcare-Associated Pathogen

Abstract: Genome sequencing has been useful to gain an understanding of bacterial evolution. It has been used for studying the phylogeography and/or the impact of mutation and recombination on bacterial populations. However, it has rarely been used to study gene turnover at microevolutionary scales. Here, we sequenced Mexican strains of the human pathogen Acinetobacter baumannii sampled from the same locale over a 3 year period to obtain insights into the microevolutionary dynamics of gene content variability. We found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
53
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 63 publications
5
53
2
Order By: Relevance
“…Given that the SNP-based analysis was focused on the core genes of these isolates, we also constructed a dendrogram according to the presence and absence of accessory genes. Importantly, the distribution of isolates between the different clades did not fully align with their presentation in the SNP-based phylogenetic tree; although other groups have reported similar discrepancies (Orsi et al, 2011;Anastasi et al, 2016;Graña-Miraglia et al, 2017;Henri et al, 2017). Several reasons may account for this observation, such as natural factors including horizontal gene transfer and recombination, and technical factors including gaps in the draft genomes and inaccurate parameters for the pan-genome estimation (Orsi et al, 2011;Rouli et al, 2015).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Given that the SNP-based analysis was focused on the core genes of these isolates, we also constructed a dendrogram according to the presence and absence of accessory genes. Importantly, the distribution of isolates between the different clades did not fully align with their presentation in the SNP-based phylogenetic tree; although other groups have reported similar discrepancies (Orsi et al, 2011;Anastasi et al, 2016;Graña-Miraglia et al, 2017;Henri et al, 2017). Several reasons may account for this observation, such as natural factors including horizontal gene transfer and recombination, and technical factors including gaps in the draft genomes and inaccurate parameters for the pan-genome estimation (Orsi et al, 2011;Rouli et al, 2015).…”
Section: Discussionmentioning
confidence: 86%
“…The output of Prokka was used to construct the pan-genome using Roary v3.11.2, with a BLASTP identity cutoff of 90% . A profile of absence (0) or presence (1) of all genes was generated according to the pangenome distribution of all samples, and a hierarchically clustered heatmap was created with this matrix by using the Pearson correlation function in R (Graña-Miraglia et al, 2017).…”
Section: Pan-genome Analysismentioning
confidence: 99%
“…We want to highlight that the biology of the species under consideration could have a very important effect on the number of orthologous genes found. For instance, highly recombinogenic species, such as Neisseria gonorrhoeae ( Ezewudo et al, 2015 ) and Acinetobacter baumannii ( Grana-Miraglia et al, 2017 ), would have fewer orthologous genes than more clonal species. Nonetheless, the strategy employed by us should work even in these species, although the number of potential orthologous genes should be much less.…”
Section: Discussionmentioning
confidence: 99%
“…Several are the studies where has been demonstrated by NGS analysis the high degree of variation in A . baumannii clinical isolates, including single nucleotide polymorphisms (SNPs) and large DNA fragment variations in the resistance island (RI) regions, the type VI secretion system (T6SS) and the bacteriophages 27 , 28 . One of the key determinants of the size, composition, structure and development of a microbial community is the predation pressure exerted by bacteriophages 29 .…”
Section: Discussionmentioning
confidence: 99%